Jurisdiction and applicable law to claims related to the payment of contributions to the budget of an association of property owners for the maintenance of the communal areas of a building. Comment on the judgment of the Court of Justice of the European Union of 8 May 2019, Brian Andrew Kerr v Pavlo Postnov and Natalia Postnova, C-25/18 - Echebarría Fernández, Jonatan (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
This comment on the judgment C-25/18 analyses the characterisation of the outstanding amounts payable by the owners of an apartment to the manager of the association of owners of the building in concept of maintenance costs of communal areas. The Court of Justice of the European Union identifies the court having jurisdiction according to Article 7(1)(a) (matters related to contract) of the Brussels I Recast Regulation and the applicable law according to Articles 4(1)(b) (provision of services). However, Article 4(1)(c) (rights in rem in immovable property) of the Rome I Regulation is not applicable.